2005
DOI: 10.1128/jb.187.17.5927-5936.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogeny of Bacterial RNA Nucleotidyltransferases: Bacillus halodurans Contains Two tRNA Nucleotidyltransferases

Abstract: We have analyzed the distribution of RNA nucleotidyltransferases from the family that includes poly(A) polymerases (PAP) and tRNA nucleotidyltransferases (TNT) in 43 bacterial species. Genes of several bacterial species encode only one member of the nucleotidyltransferase superfamily (NTSF), and if that protein functions as a TNT, those organisms may not contain a poly(A) polymerase I like that of Escherichia coli. The genomes of several of the species examined encode more than one member of the nucleotidyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 41 publications
(64 reference statements)
1
42
0
Order By: Relevance
“…10B). Thus, as previously observed (24), poly(A) polymerase is surprisingly nonspecific: The enzyme can add an A residue to immature tRNA-NCC in vivo (19), augmenting tRNA repair by the CCA-adding enzyme, but it can also add a poly(A) tail to mature tRNA in vitro (25) (SI Fig. 10B).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…10B). Thus, as previously observed (24), poly(A) polymerase is surprisingly nonspecific: The enzyme can add an A residue to immature tRNA-NCC in vivo (19), augmenting tRNA repair by the CCA-adding enzyme, but it can also add a poly(A) tail to mature tRNA in vitro (25) (SI Fig. 10B).…”
Section: Resultsmentioning
confidence: 70%
“…In most eubacteria, CCA addition is carried out by a single CCA-adding enzyme, but in the deeply branching eubacteria Aquifex aeolicus and Deinococcus radiodurans (17,18), and possibly in the Gram-positive eubacterium Bacillus halodurans (19), related CC-and A-adding enzymes work sequentially to add CCA. All of these eubacterial CCA-, CC-, and A-adding enzymes, as well as eubacterial poly(A) polymerase and eukaryotic CCA-adding enzymes, belong to the same class II NTR superfamily (6,17,19,20); moreover, a sequence alignment of the nucleotide binding region (helices F and G) in class II enzymes (SI Fig. 5) reveals that the protein template residues in the BstCCA enzyme (E153, D154, and R157) are conserved in the A. aeolicus CC-adding enzyme (E164, D165, and R168) and A-adding enzyme (E583, D584, and R587).…”
Section: Resultsmentioning
confidence: 99%
“…In organelles, the tRNA nucleotidyltransferase only has to add two nucleotides, C and A, to the 39 end because a high number of plastid tRNA genes encode a C at the 39 end (Mayer et al, 2000;Tomita et al, 1996). Aquifex aeolicus, Deinococcus radiodurans, some cyanobacteria and recently Bacillus halodurans, Bacillus clausii and Geobacter sulfurreducens have been found to contain separate enzymes for the addition of A and C residues to tRNA in vivo (Bralley et al, 2005(Bralley et al, , 2009Neuenfeldt et al, 2008;Seth et al, 2002;Tomita & Weiner, 2001. In Streptomyces coelicolor less than a third of the tRNA genes encode the CCA end and the product of SCO3896, the S. coelicolor CCase, is essential in this process (Bralley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In some organisms a single CCase modifies the 39 end of damaged or immature tRNAs in a template-independent manner. Interestingly, it has been shown that in Aquifex aeolicus (Tomita & Weiner, 2001), Synechocystis sp., Deinococcus radiodurans (Tomita & Weiner, 2001), Bacillus halodurans (Bralley et al, 2005), Bacillus clausii (Neuenfeldt et al, 2008) and Geobacter sulfurreducens (Bralley et al, 2009) there are two enzymes, one of which adds the CC dinucleotide and one that adds the terminal A. In B. subtilis there is only a single gene coding for CCase (Raynal et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation